Nocardia proteolytioa N. SP. - Joly, S. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1970)
This paper deals with a Nocardia strain isolated from soil. Indeed an attemp to classified it was made, but it was not accomplished, because this strain differs from those described in the Manual of Determinative Bacteriology(BREED, 1957). The name Nocardia proteolytica n. sp. is proposed for it.